Etyka przeróbki. Internetowe reanimacje Omrana Daqneesha - Jakubowski, Piotr (Załącznik Kulturoznawczy, 2023)
This article is a follow-up of the essay Aylan Kurdi’s Online Resurrections published in the previous issue of the ‘Cultural Studies Appendix’ (3/2016). This time the author analyzes the remakes of the widely shared shot of Omran Daqneesh – a 5-years old Syrian boy sitting in the ambulance and fully covered by dust with seeable traces of brushes and stains of blood – taken from the viral footage which reported damages and sufferings caused by the airstrikes on the Syrian biggest city, Aleppo, during the civil war. For once the author discusses not only the visual rhetoric strategies applied in those remakes, but also their ethical dimensions, especially in reference to the category of ‘unrepresentability’ connected with the concept of the ‘limit situations’.